Pengaruh Disiplin dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Atena Bangun Mandiri - Nurholisa Nurholisa; Herayati Herayati; Vicky Windasari (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
In an era of increasingly fierce business competition, companies are required to continuously improve the quality of human resources as a strategic asset. Superior human resources are one of the main keys in determining the success and competitiveness of a company. One important indicator in measuring the quality of human resources is employee performance. Optimal performance reflects the effectiveness and efficiency of task implementation as well as a real contribution to the achievement of organizational goals. This study aims to analyze the influence of work discipline and motivation on employee performance at PT. Atena Bangun Mandiri, a company engaged in the construction and procurement sector. The research method used is a quantitative approach with a descriptive and associative research design. The population in this study were all 56 employees of PT. Atena Bangun Mandiri, where the sampling technique was carried out using saturated sampling, because the entire population was sampled. Data were collected through closed questionnaires compiled based on research variable indicators, then processed and analyzed using SPSS statistical software. The results showed that work discipline has a partial significant influence on employee performance with a contribution of 20.7%. This means that the higher the level of employee discipline, the more their performance tends to increase. Meanwhile, work motivation also had a significant partial effect of 50.8%, indicating that motivation plays a dominant role in driving work enthusiasm and productivity. Simultaneously, work discipline and motivation significantly influenced employee performance. The implications of this study demonstrate the importance of managerial strategies to increase motivation through reward systems, opportunities for self-development, and creating a comfortable work environment. Furthermore, consistent implementation of work discipline must also be maintained to foster a professional and results-oriented work culture.